Hedging and ambiguity - Oechssler, Joerg; Rau, Hannes; Roomets, Alex (Discussion paper series, 2016)
We run an experiment that gives subjects the opportunity to hedge away ambiguity in an Ellsberg-style experiment. Subjects are asked to make two bets on the same draw from an ambiguous urn, with a coin flip deciding which bet is paid. By modifying the timing of the draw, coin flip, and decision, we are able to test the reversal-of-order axiom, particularly as it relates to the ability of the Random-Lottery Incentive System (RLIS) to prevent cross-task contamination in an ambiguity setting. We find that we cannot reject that the reversal-of-order axiom holds. This suggests that hedging could still be possible when carefully implementing RLIS. However, we also find low levels of ambiguity hedging across the board, suggesting the existence of the hedging possibility does not necessarily represent a common problem in ambiguity experiments.